2017
DOI: 10.4338/aci-2017-07-r-0116
|View full text |Cite
|
Sign up to set email alerts
|

Patient Self-Management of Asthma Using Mobile Health Applications: A Systematic Review of the Functionalities and Effects

Abstract: Objective The aim of this systematic review was to summarize the evidence regarding the effects of mobile health applications (mHealth apps) for self-management outcomes in patients with asthma and to assess the functionalities of effective interventions. Methods We systematically searched Medline, Scopus, and the Cochrane Central Register of Controlled Trials. We included English-language studies that evaluated the effects of smartphone or tablet computer apps on self-management outcomes in asthmatic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 43 publications
1
74
0
11
Order By: Relevance
“…In brief, a checklist was constructed to determine the information content and functionalities of the asthma self-management application based on the selected guideline from the previous stage and a systematic review conducted by the authors in this field. 28 The content validity of the checklist confirmed separately by specialists in the field of health information management (two people), nurse (eight people), and asthma and allergy specialists (five people). The minimum acceptable Content Validity Ratio (CVR) value for 15 participants was 0.42 based on the Lawshe's table and 0.79 for the Content Validity Index (CVI).…”
Section: Determining Information Content and Functionalitiesmentioning
confidence: 90%
See 1 more Smart Citation
“…In brief, a checklist was constructed to determine the information content and functionalities of the asthma self-management application based on the selected guideline from the previous stage and a systematic review conducted by the authors in this field. 28 The content validity of the checklist confirmed separately by specialists in the field of health information management (two people), nurse (eight people), and asthma and allergy specialists (five people). The minimum acceptable Content Validity Ratio (CVR) value for 15 participants was 0.42 based on the Lawshe's table and 0.79 for the Content Validity Index (CVI).…”
Section: Determining Information Content and Functionalitiesmentioning
confidence: 90%
“…With regard to the importance of training in daily asthma management, and the role of mobile applications in improving self-management, [28][29][30] and also the lack of reliable information in these applications, [23][24][25] designing an evidence-based application to promote self-management seems to be necessary. Therefore, the aim of this study was to design a mobile application based on the guideline, evaluate its usability by performing user evaluation, and examine its effects on their knowledge.…”
Section: Objectivesmentioning
confidence: 99%
“…Health systems should consider the appropriateness of other solutions both internal and external to the EHR, such as text reminders or behavioral nudges sent to patients. [7][8][9][10]…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Approximately 20 to 30% of antihypertensive, antihyperlipidemic, antihyperglycemic prescriptions, and other chronic medications are never filled, and 50% are not taken as prescribed. [5][6][7][8][9][10] Additionally, 19% of patients intentionally miss or halve medications to reduce prescription costs. 11 In practice, clinicians tend to overestimate medication adherence and underestimate the proportion of patients with cost barriers.…”
Section: Background and Significancementioning
confidence: 99%
“…Previous studies have demonstrated that the quality of asthma care provided by specially trained asthma nurses (nurse-led asthma care) was equal to that provided by physicians, with an additional advantage of reducing medical expenses (Kamps et al, 2004;Kuethe, Vaessen-Verberne, Elbers, & Van Aalderen, 2013). Studies also showed that appropriate asthma management measures to ensure patient treatment adherence could significantly improve clinical outcomes for children with asthma (Farzandipour, Nabovati, Sharif, Arani, & Anvari, 2017; Global Initiative for Asthma, 2017; Morton et al, 2017). Computer and internet applications are more frequently applied in health care these days and asthma management programs adopting technological interventions to encourage patient engagement could improve asthma management (Arnold, Stingone, & Claudio, 2012;Katwa & Rivera, 2018;Morita et al, 2019;Trivedi, 2015;Voorend-van Bergen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%